2008
DOI: 10.1111/j.1540-8159.2008.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring of CRT‐ICD: The Multicenter Italian CareLink Evaluation—Ease of Use, Acceptance, and Organizational Implications

Abstract: The ease of use, satisfaction, and acceptance of the CareLink Network in European clinical practice appears elevated both for patients and for clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 13 publications
4
74
1
6
Order By: Relevance
“…14 Moreover, it has been suggested that, by improving the clinical management of tachyarrhythmias and HF episodes in ICD patients, 15 remote monitoring could lead to a reduction in healthcare use. In particular, it could be effective in decreasing unplanned in-office visits, which are more costly than scheduled visits in terms of time dedicated by specialized personnel because they take Ϸ30% longer.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, it has been suggested that, by improving the clinical management of tachyarrhythmias and HF episodes in ICD patients, 15 remote monitoring could lead to a reduction in healthcare use. In particular, it could be effective in decreasing unplanned in-office visits, which are more costly than scheduled visits in terms of time dedicated by specialized personnel because they take Ϸ30% longer.…”
Section: Discussionmentioning
confidence: 99%
“…Uma análise de qualidade de vida com o questionário SF-36 mostrou que 93 a 97% dos doentes se encontram satisfeitos com a conveniência e exequibilidade do sistema de monitorização à distância 27 . Diferentes estudos, em doentes com CDI ou com TRC-D, revelaram níveis de satisfação elevados quer nos doentes, que nos médicos 11,28 .…”
Section: Custo-benefício Da Monitorização à Distânciaunclassified
“…Several studies have shown a high degree of patient satisfaction with the convenience and ease of use of remote monitoring systems (Marzegalli et al, 2008, Masella et al, 2008, Raatikainen et al, 2008. From a patient's perspective, the biggest value of remote monitoring is convenience with fewer in-clinic visits and less time traveling to and from their clinics.…”
Section: Patient Preferencementioning
confidence: 99%
“…Remote monitoring also leads to greater patient reassurance and improved patient follow-up adherence (Varma et al, 2010). Most patients prefer remote monitoring over in-clinic visits (Marzegalli et al, 2008, Masella et al, 2008. In TRUST trial, 98% of patients elected to retain remote monitoring as a follow-up mode on trial conclusion (Varma et al, 2010).…”
Section: Patient Preferencementioning
confidence: 99%